2006
DOI: 10.1002/14651858.cd003983.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy for the treatment of refractory high intracranial pressure in traumatic brain injury

Abstract: There is no evidence to support the routine use of secondary DC to reduce unfavourable outcome in adults with severe TBI and refractory high ICP. In the pediatric population DC reduces the risk of death and unfavourable outcome. Despite the wide confidence intervals for death and the small sample size of the only study identified, this treatment maybe justified in patients below the age of 18 when maximal medical treatment has failed to control ICP. To date, there are no results from randomised trials to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(145 citation statements)
references
References 93 publications
2
133
0
10
Order By: Relevance
“…Traumatic brain injury (TBI), which is also known as head injury (1)(2)(3), is a leading cause of mortality and morbidity (1,(4)(5)(6), especially among those of young ages (1).…”
Section: Contextmentioning
confidence: 99%
“…Traumatic brain injury (TBI), which is also known as head injury (1)(2)(3), is a leading cause of mortality and morbidity (1,(4)(5)(6), especially among those of young ages (1).…”
Section: Contextmentioning
confidence: 99%
“…Although prompt relief of ICH has been consistently documented, evidence for improved overall outcome is lacking [62], In fact, The Decompressive Craniectomy in Diffuse TBI (DECRA) trial reported a higher mortality in patients randomized to undergo surgical decompression compared with those randomized to undergo continued medical management when ICPs remained greater than 20 mmHg for 15 min [8]. However, as mentioned earlier, the threshold may have been set too low to make this a clinically relevant study, and debate regarding the usefulness of the procedure continues [63].…”
Section: Decompressive Craniectomymentioning
confidence: 99%
“…Prophylactic or primary DC is defined as the surgical decompression performed primarily for evacuation of an underlying mass of any type, whenever the surgeon decides that removal of the bone flap along with the overlying bone flap will benefit the patient. According to the Congress of Neurological Surgeons' guidelines, a prophylactic DC may be performed in: a) comatose patients with epidural hematoma, b) in patients with acute subdural hematoma with thickness greater than 10 mm, or midline shift greater than 5 mm, c) in patients with admitting GCS score <8 and traumatic parenchymal lesions greater than 50 cm 3 in volume, or greater than 20 cm 3 with midline shift of at least 5 mm and/or cisternal compression, and d) in patients with open (compound) depressed cranial fractures, greater in thickness than that of the adjacent cranium, or with underlying hematoma, dural penetration, pneumocephalus, infection, or frontal sinus involvement [Bullock, et al, 2006;Sahuquillo & Arikan, 2006]. Secondary DC or therapeutic decompression is defined as the surgical decompression performed in patients with massive unilateral or bilateral brain edema in order to control high ICP refractory to maximal medical therapy.…”
Section: Types Of Surgical Decompression and Surgical Proceduresmentioning
confidence: 99%
“…The most important controversial points may be summarized to the following:  Lack of clear indications and guidelines, regarding the selection of candidates for DC. Cochrane data base analysis in 2007 [Sahuquillo & Arikan, 2006] concluded that there was no evidence to support the routine use of secondary DC to reduce unfavorable outcome in adults suffering S-TBIs and refractory intracranial hypertension. Contrariwise, it seems that there is more solid evidence in pediatric trauma patients, in whom DC seems to reduce the risk of death and unfavorable outcome [Sahuquillo & Arikan, 2006] before irreversible brain stem compression and/or herniation occur [Ruf, et al, 2003;Timofeev, et al, 2008].…”
Section: Current Concepts and Controversiesmentioning
confidence: 99%